UNTUK MENINGKATKAN KEBERANIAN BERBICARA PADA SISWA KELAS IV SD N JETIS 2 YOGYAKARTA - Haryati, Sri (TAMAN CENDEKIA: Jurnal Pendidikan Ke-SD-an, 2018)
This research is aimed to grasp understanding about the improvement of students' courage in speaking through show and tell activity by using media of images for the 4th grader students in Jetis 2 Public Elementary School Yogyakarta. This is an action classroom research, which has been conducted in 2 cycles. Each cycle consists of 3 meetings. The subject of this research is all 4th grader students of Jetis 2 Public Elementary School Yogyakarta, academic year of 2014/2015, which consists of 12 students, 6 male students and 6 female students. The data collecting techniques employed are observation and working performance by using indicator matrix of students' speaking courage, the skill of showing and telling and also the process of show and tell activities in class.In addition, this research also employs documentation technique, in the form of photos during the occurrence of the research process. The analysis technique in this research uses descriptive qualitative technique. The results of the research are presented as follow: show and tell method can improve the students' speaking courage 23,61% (formerly it was 55,38% reaching up to 78,99%), the skill of show and tell of 27,43% (from 56,25% reaching up to 83,68%) and the process show and tell is 9,03% (from 72,91% reaching up to 81,94%).